The Effect of Oxytocin Massage in the Active Phase of 1 Period On the Length of Labor - Ernida, Yulia; Maritalia, Dewi; Rahmah, Siti; Nuraina, Nuraina (LPPM STIKes Muhammadiyah Ciamis, 2024)
Introduction: Prolonged labor is one of the causes of maternal and fetal death; in the mother there will be infection, dehydration, exhaustion, and postpartum hemorrhage, while in the fetus there will be infection, injury, and asphyxia. This is one of the causes of prolonged labor; in the labor process, inadequate conditions will trigger prolonged labor. Oxytocin massage during labor will produce good uterine contractions so that it can speed up the labor process. Objective: The aim of this study was to describe the effect of oxytocin massage during the active phase of the first stage of labor on the length of labor. Method: This study is an experimental study with a case control. The population is all inpartu mothers who gave birth at the Independent Midwife Practice Place (TPMB) located in Bireuen Regency. The sampling technique used purposive sampling with inclusion criteria: being in the active phase of stage I, accompanied by a husband or family during the labor process, willing to do oxytocin massage for at least 15 minutes in the active phase of stage I. The number of samples was 30, which were divided into 2 groups, namely: 15 respondents were given treatment in the form of oxytocin massage in the active phase of stage 1 by their husband or family for 15 minutes in the mother's left side sleeping position (experimental group) and 15 respondents as control cases (case control). Result: The results of the Independent Sample T-Test Sig. (2-tailed) statistical test were 0.000, which is <0.05, so it can be concluded that there is an effect of oxytocin massage in the active phase of the first stage on the length of labor. Conclusion: It is hoped that related parties such as health workers and families can increase the provision of oxytocin massage to mothers in labor so that it can speed up the labor process.